PENDIDIKAN KEMANDIRIAN BERBASIS KEWIRAUSAHAAN - Rusi Rusmiati Aliyyah; Siti Rahmah (Universitas Djuanda, 2017)
Penelitian ini bertujuan untuk mendeskripsikan fungsi manajemen diantaranya perencanaan, pelaksanaan, pengawasan pendidikan kemandirian dan kewirausahaan pondok pesantren. Penelitian menggunakan pendekatan kualitatif studi kasus. Data dikumpulkan melalui observasi, wawancara, dokumen, dan merekam informasi. Teknik analisis data menggunakan model analisis Miles Huberman melalui komponen analisis berupa reduksi data, penyajian data, serta kesimpulan atau verifikasi. Hasil penelitian menyatakan perencanaan pendidikan kemandirian berbasis kewirausahaa dibuat oleh tim penyelenggara diantaranya pimpinan pesantren, ketua umum yayasan, kepala sekolah, dan guru. Perencanaan dibuat berdasarkan analisis kebutuhan dan kepentingan organisasi. Pelaksanaan pendidikan kemandirian berbasis kewirausahaan dilakukan melalui suri tauladan dari seluruh pengelola pesantren, dilakukan melalui pembiasaan, penugasan, pelaksanaan pendidikan kemandirian berbasis kewirausahaan termasuk dalam kegiatan Ta’aruf. Pengawasan pendidikan kemandirian berbasis kewirausahaan dilakukan oleh seluruh pengelola pesantren, pengawasan diberikan secara akademik dan manajerial, serta pengawasan melalui rapat konsultasi, dan koordinasi.KATA KUNCI: Pendidikan, Kemandirian, dan KewirausahaanINDEPENDENCE EDUCATION BASED ON ENTREPRENEURSHIP EDUCATIONABSTRACTIndependent Character Education has a purpose of confidence in carrying out an affair. This self-reliance education spurred the courage of someone in action, not resigned and frozen, but dynamic, energetic and always optimistic toward the future. Through Entrepreneurship it is a provision of santri or students in the future with the added value in the market, through the process of combining resources through different new ways, in order to compete. The purpose of this research is to describe the management function such as planning, implementation, supervision of self-reliance education, entrepreneurship of Darussyifa Al-Fithroh Sukabumi pesantren. The research used qualitative approach of case study. Data are collected through observation, interviews, documents, and recording / recording information. Data analysis techniques on research using Miles Huberman analysis model, the analysis component in the form of data reduction, data presentation, and conclusion or verification. The result of the research states that self-reliance education based on entrepreneurship planning is made by the team of pesantren, among them the leadership of pesantren, the chairman of the foundation, the heads, the teachers, the planning made the aspect of needs and interests, and determines the teachers who are capable in the implementation of the activities. The implementation of entrepreneurship based self-reliance education is done through the role model of all pesantren managers, conducted through habituation, assignment, implementation of entrepreneurial based self-reliance education included in Ta'aruf activities. The supervision of entrepreneurship based autonomy education is carried out by all board managers, supervision is given academically and managerially, and supervision through consultation meeting, coordination.